Implementation of risk mitigation among IT governance practitioners in Malaysia - Anthony Jnr, Bokolo; Che Pa, Noraini; Nor, Rozi Nor Haizan; Jusoh, Yusmadi Yah; Mohd Aris, Teh Noranis (American Scientific Publishers, 2018)
IT industry is facing risks that make IT projects not able reach the scheduled and quality. Therefore, there is an important for risk mitigation in IT Governance to support IT team. Risk mitigation provides expert assistance during IT project activities in supporting team members and decision makers to identify risks associated with in IT process by providing risk documentation of probability and impact of IT risks. Risk mitigation introduces risk advice and designing appropriate strategic alternatives to treat the risk by providing support for the reuse of knowledge. There are, numerous studies have been suggested for seeing the issues in risk mitigation. This paper is a contribution to study on implementation of risk mitigation people management, process management, technology management and quality management involved in IT Governance. The findings of this review indicate that there are some limitations experienced by IT practitioners in mitigating risk effectively.